KEGIATAN EKSTRAKURIKULER KALIGRAFI UNTUK MENGEMBANGKAN KREATIVITAS SISWA DALAM MENULIS AYAT AL-QUR’AN (STUDI KASUS DI LBE AL-RIFA’IE) - Desy Dwi Cahyani; Anwar Sa’dullah; Eko Setiawan (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Extracurricular activities are activities outside of learning hours to hone the interests, talents and creativity of students. Creativity is very important in learning, especially in the development of writing verses of the Qur'an through calligraphy. The focus of this research: implementation, process, obstacles experienced during the process of implementing calligraphy extracurricular activities at LBE Al-Rifa'ie. This study uses a qualitative approach, with the type of case study, data collection techniques by conducting interviews, observation and documentation. Based on the research results, namely: 1) The implementation of calligraphy extracurricular activities at LBE AlRifa'ie is carried out once a week every Friday. The material given in each meeting is different and uses the Learning by Doing method. 2) The implementation process is carried out in the early stages, students are given knowledge about the basics of writing khat, good and correct writing rules, students are given examples by the supervising teacher, then students will imitate it on a sheet of paper, given the freedom to make works according to their respective creative ideas. 3) Constraints experienced during the process of extracurricular activities take place, namely in terms of facilities.